Nutrition therapy in esophageal cancer—Consensus statement of the Gastroenterological Society of Taiwan. Issue 8 (31st May 2018) - Chen, M-J; Wu, I-C; Chen, Y-J; Wang, T-E; Chang, Y-F; Yang, C-L; Huang, W-C; Chang, W-K; Sheu, B-S; Wu, M-S; Lin, J-T; Chu, C-H
SUMMARY: A number of clinical guidelines on nutrition therapy in cancer patients have been published by national and international societies; however, most of the reviewed data focused on gastrointestinal cancer or non-cancerous abdominal surgery. To collate the corresponding data for esophageal cancer (EC), a consensus panel was convened to aid specialists from different disciplines, who are involved in the clinical nutrition care of EC patients. The literature was searched using MEDLINE, Embase, the Cochrane Central Register of Controlled Trials, and the ISI Web of Knowledge. We searched for the best evidence pertaining to nutrition therapy in the case of EC. The panel summarized the findings in 3 sections of this consensus statement, based on which, after the diagnosis of EC, an initial distinction is made between the patients, as follows: (1) Assessment; (2) Therapy in patients with resectable disease; patients receiving chemotherapy or chemoradiotherapy prior to resection, and patients with unresectable disease, requiring chemoradiotherapy or palliative therapy; and (3) Formula. The resulting consensus statement reflects the opinions of a multidisciplinary group of experts, and a review of the current literature, and outlines the essential aspects of nutrition therapy in the case of EC. The statements are: Patients with EC are among one of the highest risk to have malnutrition. Patient generated suggestive global assessment is correlated with performance status and prognosis. Nutrition assessment for patients with EC at the diagnosis, prior to definitive therapy and change of treatment strategy are suggested and the timing interval can be two weeks during the treatment period, and one month while the patient is stable. Patients identified as high risk of malnutrition should be considered for preoperative nutritional support (tube feeding) for at least 7–10 days. Various routes for tube feedings are available after esophagectomy with similar nutrition support benefits. Limited intrathoracic anastomotic leakage postesophagectomy can be managed with intravenous antibiotics and self-expanding metal stent (SEMS) or jejunal tube. Enteral nutrition in patients receiving preoperative chemotherapy or chemoradiation provides benefits of maintaining weight, decreasing toxicity, and preventing treatment interruption. Tube feeding or SEMS can offer nutrition support in patients with unresectable esophageal cancer, but SEMS is not recommended for those with neoadjuvant chemoradiation before surgery. Enteral immunonutrition may preserve lean body mass and attenuates stress response after esophagectomy. Administration of glutamine may decrease the severity of chemotherapy induced mucositis. Enteral immunonutrition achieves greater nutrition status or maintains immune functions during concurrent chemoradiation.